Parathyroid Adenoma: A Case Report with Unusual Clinical Features - Islam, Urnas; Ferdous, Jasmin; Jabin, Zeenat; Reza, Sharmin; Begum, Fatima (Bangladesh Journal of Nuclear Medicine, 2019)
Abstract not available. Bangladesh J. Nuclear Med. 22(1): 61-63, Jan 2019